Lending Calling. Recession by Over-Indebtedness: Description and Specific Features of the Spanish Case - Martín, Antonio Sanabria; García, Bibiana Medialdea (Panoeconomicus, 2016)
Following the approaches of Fisher, Koo, and in particular Minsky, this article describes recent developments in the Spanish economy. These authors’ theories of financial fragility, and the extension of analysis of the recession to also include the expansionary period, are very useful when it comes to understanding the boom (1994-2008) and subsequent collapse of the Spanish economy. Both processes are part of the same phenomenon: the binomial relation between debt and the asset bubble, amplified by the use of external financing, and the subsequent process of slow deleveraging. Alongside said analytical elements, and considering Spain’s membership in the Eurozone monetary union system, this characterisation of the euphoria and subsequent balance-sheet recession further identifies specific features of the Spanish economy that informed current outcomes.Key words: Over-indebtedness, Recession, Deleveraging, Spain.JEL: E6, F4, F5.